기후변화대비 지속가능 발전방안 - 김연중 (한국농촌경제연구원, 2008)
As a result of climate change, the main production areas of agriculture are changing, affecting the productivity and quality of crops. And the damages by blight and harmful insects have increased and the agricultural ecosystem is disturbed. After all, the method and time of cultivation, fertilization methods, irrigation management, and crop species will be changed. The purposes of this research are to analyze the impacts of climate change on agriculture, livestock, forestry and the regional festival of Hwacheon and to derive long-term countermeasures. The main contents of this research are as follows: the present condition and the prospect of climate change in the inside and outside of the country, the impacts of climate change on agriculture, the current condition and the outlook for the main products of Hwacheon, the issues and improvement methods of "Sancheoneo Festival," and their future directions. This research also investigated the farmhouses cultivating the main crops of Hwacheon and tried to grasp the changes in production amount, income, the damage level caused by blight and harmful insects, flowering time, harvest time, etc. due to climate change. The Sancheoneo Festival, which takes place every year in Hwacheon, was the first of all “the festivals” held in Korea and it is the most popular winter festival in Korea. But the change in ice thickness due to the recent rise in temperature has raised the concern that it would threaten the festival’s success. So, this research proposed sustainable development strategies for the festival. Finally, we recommended the following policies to prepare for the climate change: installation and operation of the AWS (Automatic Weather System), use of insect resources, setting up of plans to better coordinate and strengthen government policies on global warming adaptation, and establishment of mid- and long-term countermeasures. Researcher: Yean-Jung Kim, Woong-Yeon Lee, Jin-Nyoun Kim E-mail address: yjkim@krei.re.kr